Regulation of Myosin Heavy Chain Expression during Rat Skeletal Muscle Development In Vitro - Torgan, Carol E. (The American Society for Cell Biology, 2001)
Signals that determine fast- and slow-twitch phenotypes of skeletal muscle fibers are thought to stem from depolarization, with concomitant contraction and activation of calcium-dependent pathways. We examined the roles of contraction and activation of calcineurin (CN) in regulation of slow and fast myosin heavy chain (MHC) protein expression during muscle fiber formation in vitro. Myotubes formed from embryonic day 21 rat myoblasts contracted spontaneously, and ∼10% expressed slow MHC after 12 d in culture, as seen by immunofluorescent staining. Transfection with a constitutively active form of calcineurin (CN*) increased slow MHC by 2.5-fold as determined by Western blot. This effect was attenuated 35% by treatment with tetrodotoxin and 90% by administration of the selective inhibitor of CN, cyclosporin A. Conversely, cyclosporin A alone increased fast MHC by twofold. Cotransfection with VIVIT, a peptide that selectively inhibits calcineurin-induced activation of the nuclear factor of activated T-cells, blocked the effect of CN* on slow MHC by 70% but had no effect on fast MHC. The results suggest that contractile activity-dependent expression of slow MHC is mediated largely through the CN–nuclear factor of activated T-cells pathway, whereas suppression of fast MHC expression may be independent of nuclear factor of activated T-cells.